Sistem Informasi Manajemen Dan Keuangan Masjid Berbasis Website - Rizki, Alfin; Ekawati, Nia (Journal of Informatics and Electronics Engineering; Vol 3 No 2 (2023): Desember 2023DO - 10.70428/jiee.v3i2.780, 2023)
The Great Mosque of Al-Muhajirin founded in 2013 is one of the Jami Mosque categories, which usually functions as a center for religious activities in residential areas, villages or sub-districts. However, until now, this mosque does not yet have an integrated information system to manage activities, disseminate information, process finance and process data accurately. This deficiency complicates management in mosque management. To overcome these problems or deficiencies, a website-based mosque management and financial information system was created using the Hypertext Preprocessor (PHP), the CodeIgniter framework and using the MySQL database. The stages of the research include needs analysis, system design, system implementation and system testing using the blackbox method and user acceptance test (UAT). UAT results show that 92% of respondents and the community stated that the website was suitable for use by the wider community. This system makes it easy for mosque administrators to manage mosque management effectively and provides accessibility for the public to get information about mosque announcements and activities from anywhere and at any time. With the creation of this information system, the Great Mosque of Al-Muhajirin will be more efficient and open in managing activities, information and finances as well as getting closer to the wider community .